A brownfield lean conversion: a case study of Opel Belgium. (14th January 2008) - Mothersell, William M.; Moore, Michael L.; Strolle, Mark
This case study examined the brownfield conversion from mass to lean production in a large automotive company. This case presents the critical factors in the lean transformation of the Opel Belgium (OB) plant, which is located in Antwerp approximately 30 miles from Brussels. This case offers a coherent transformational model for converting brownfield sites into lean production facilities. The model includes key technical components in the lean conversion, which includes changes in assembly layout, changes in takt time, jobs per hour as well as other technical elements. The change to lean also identifies and discusses culture and people system, change efforts instrumental to this change. Some of the key elements include creating a common vision for lean, establishing people systems in harmony with lean and parallel organisational structures.